Energy Policy, or Lack Thereof - Turner , Wayne C. (Strategic Planning for Energy and the Environment, 2023)
Our country badly needs a national energy policy. Each of us has our opinions as to what should be done, and we’re probably all correct and all wrong. In other words, there is no one answer. However, to drift through such a critical time period without a stated energy policy is an indication of a lack of coordinated leadership. We can’t change that, but we can provide a forum for a discussion of national energy policy, and that is one of our goals for a future issue. I am in the process of contacting those with firm views (whatever direction that view leans) and offering an issue of this journal as a forum to air those views. We have some great leaders and ideas on all sides of this question, and it will be enlightening to see in one publication what everyone has to say. I am asking that we ignore the short-term situation (e.g. whether the energy bill passes or not) and concentrate on “what should be.” Obviously, each of us cannot write an article (the issue would be pretty large with over 11,000 articles), but perhaps some of you know someone that should be an author. Alternatively, maybe you would like to write a letter to the editor (me) expressing your views. I will try to publish as many of those as possible, but please be patient with us. My goal is to make this forthcoming issue the publication that is on the desk of most energy policy decision makers. Thus, it will be well read if I do my job properly. Help me make this work. Contact anyone you think should contribute, or give the name to me and I will contact them. You know, this could be one of the most important things we ever do, and it could have long lasting impacts. Let’s do it properly. Good luck in your endeavors and please let me hear from you.